Entre a inclusão e a diversidade: um estudo sobre a implementação da política de cotas na UFC - Freire, João Victor de Farias Furtado e (2016)
This dissertation aims to analyze the implementation of the quota system at the Federal University of Ceará. Therefore, the debate starts on the very creation of this affirmative action. The research used data obtained from the meetings of the Working Group of 2005 and the Affirmative Action Policy Group 2005/2006 and interviews with key characters of these debates, to build the trajectory of the implementation of the quota system before the approval of Quota Law in 2012. It also conducted field work through a participant observation in anthropology classes and Public Policy course in Management in Public Policy. The importance of contact with these quota students, consisted in the fact that they were one of the first students after adopting 50% of vacancies for unitholders of the UFC. Then, through interviews, build trajectories of 3 quota students, which analyzed the effects of public policy in their lives and in their own university space. This dissertation concludes, through all the data and reports obtained during the research and the reports of quota students, that the quota system is an important affirmative action to include students who hardly would obtain places in public higher education, but potentially it can be a key tool for the affirmation of a difference of politics at university.